Analysis of Community Satisfaction Levels using the Neural Network Method in Data Mining - Hasibuan, Sabdi Albi; Sihombing, Volvo; Nasution, Fitri Aini (Politeknik Ganesha Medan, 2023)
Data mining is a process that is carried out to extract data into information. There are several models that can be done in data mining, such as classification, association, clustering, regression. But in this study will be carried out using a classification model. Research conducted on the level of public satisfaction for shopping on the Lazada application. This study aims to determine the level of public satisfaction on the Lazada application. This research was also conducted because the goods sold on the Lazada application are quite cheap and when compared to the original price there is a considerable difference. Therefore, research was conducted on the level of community satisfaction on the Lazada application. This research will be conducted on data mining with a classification model and using the neural network method. The results obtained from the data mining process using 100 community data, the results obtained are 81 community data (representation obtained by 81%) of people who are satisfied shopping on the lazada application and by 19 (representation obtained by 19%) people who are not satisfied shop on the Lazada app. From these results, many people are satisfied with shopping on the Lazada app. So from the results of this classification it can be concluded that the goods sold on the Lazada application are good goods.